Low Incidence of Late Ipsilateral Ischaemic Stroke After Treatment for Symptomatic Carotid Stenosis in Sweden 2008–2017: Increased Risk in the Elderly and After Carotid Stenting. (January 2022) - Hammar, Kimberley; Laska, Ann Charlotte; Wester, Per; Mani, Kevin; Lundström, Annika; Jonsson, Magnus
Abstract : Objective: Carotid stenosis is a major risk factor for stroke and surgical treatment is key in preventing recurrent ischaemic events. Previous randomised trials have demonstrated the net benefit of surgery for significant symptomatic carotid stenosis but, with present day medical treatment, there is limited evidence on the risk of late ipsilateral ischaemic stroke (IS) and its main risk factors. Method: Ipsilateral IS after the peri-operative period (≤ 30 days) was investigated in a nationwide, registry based cohort study of patients treated for symptomatic carotid stenosis in Sweden between 2008 – 2017. The Swedish National Registry for Vascular Surgery (Swedvasc) was used to establish the cohort, and the Swedish stroke registry (Riksstroke), combined with hospital records, was used to determine outcome. Stroke of any type and all cause mortality after the peri-operative period were studied as secondary outcomes. Cox regression was used to analyse associations between clinical factors and outcomes. Results: In total, 7 589 patients (mean age 72 ± 8 years, 68% men) were followed for 4.2 ± 2.6 years. Ipsilateral IS occurred in 232 patients corresponding to a yearly incidence of 0.73%. Age above 80 years compared with 65 – 79 years was associated with an increased risk of ipsilateral IS (adjusted HR 1.94, 95% CI 1.43 – 2.65). Carotid artery stenting (CAS) compared with carotid endarterectomy (CEA) was also associated with increased risk (adjusted HR 3.20, 95% CI 2.03 – 5.03). Stroke of any type occurred in 7.7% of patients, and 19.6% of patients died during the follow up period. Conclusion: The incidence of ipsilateral IS after treatment for symptomatic carotid stenosis in Sweden 2008–2017 was low, demonstrating the effectiveness and durability of surgery in a real world setting. Only age above 80 years and CAS compared with CEA were associated with increased risk of ipsilateral IS.